Biophysics Reports - Xu, Tao
Biophysics Reports offers a worldwide forum for publishing novel theories, methods, protocols and significant improvements on basic research techniques in multidisciplinary areas of the biological and biomedical sciences. The journal welcomes submissions reporting on methods and/or techniques including but not limited to those used in: biophysics, cell biology, immunology, membrane biology, redox biology, photobiology, neurobiology, oncology, biochemistry, biomechanics and mechanobiology, structural biology, molecular imaging, electron microscopy, computational biology, bioinformatics, nano biomedicine, genetics, model organisms, protein science, developmental biology, and omics. The article types include: methods, protocols, original articles, reviews/mini-reviews, puncta, etc. As the official journal of the Biophysical Society of China, Biophysics Reports ensures an unbiased and expedient peer-reviewing process and offers open access publishing. The article-processing charges for this journal are kindly sponsored by the Biophysical Society of China and the Institute of Biophysics, CAS. As such, authors can publish in the journal without any additional charges.